306Association between polypharmacy and mortality in the community-dwelling older population: a data linkage study. (2nd September 2021) - Van der Heyden, Johan; Berete, Finaba; Devleesschauwer, Brecht; De Ridder, Karin; Bruyère, Olivier; Renard, Françoise; Charafeddine, Rana
Abstract: Background: Literature findings on the association between polypharmacy and mortality in older people are not consistent. Appropriate tools, making use of linkages, are helpful to investigate this further. Methods: Data of participants of the Belgian Health Interview Survey 2013 aged ≥ 65 years (n = 1950) were linked with billing data and 5 year's mortality follow-up information. Polypharmacy was defined as concomitant use of ≥ 5 medicines in the past 24 hours or ≥ 5 recent prescriptions of reimbursed medicines. The impact of polypharmacy on mortality was assessed through mortality rate ratios (MRR) from a Poisson regression model adjusting for gender, age, multimorbidity, functional limitations and health care use, and including interactions. Results: The prevalence of polypharmacy was 38, 3%. Age and disability status were effect modifiers in the association between polypharmacy and mortality. Whereas polypharmacy was significantly associated with mortality among people aged 65-79 years (MRR 2.52; 95% CI 1.67-3.80), this was not so for the 80 + (MRR 1.46; 95% CI 0.93-2.29). Polypharmacy was a mortality predictor among people with no/moderate functional limitations (MRR 2, 29; 95% CI 1.61-3.25), but not for those with severe functional limitations (MRR 1, 22; 95% CI 0.67-2.34). Conclusions: By linking health interview survey, billing and mortality data further insights can be gained on the association between polypharmacy and mortality. Key messages: Polypharmacy affects the mortality of people in relatively good health. A critical evaluation of polypharmacy in older people below 80 years and in people without severe functional limitations may reduce mortality in these population groups.